2016
DOI: 10.9758/cpn.2016.14.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Test of Attention in Children with Attention-Deficit/Hyperactivity Disorder in Japan for Evaluation of Methylphenidate and Atomoxetine Effects

Abstract: ObjectiveThis study was conducted to validate the Advanced Test of Attention (ATA) of the visual attention version of Japanese children with attention deficit/hyperactivity disorder (ADHD) and to evaluate the efficacy of methylphenidate (OROS-MPH) and atomoxetine medications.MethodsTo assess pharmacotherapy efficacy, the visual version of ATA was administered to 42 children with ADHD. Results were assessed using discriminant analysis, ANOVA for indices of ATA before and after medication treatment, and correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The percentage of patients showing improvement in inattention, hyperactivity, and impulsivity scores was 48.6%, 45.9%, and 45.9%, respectively. Moreover, Fujioka et al [42] reported a significant improvement in ADHD scores during the follow-up period with methylphenidate or Atomoxetine medication for inattentive symptom score, hyperactivity/impulsivity symptom.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of patients showing improvement in inattention, hyperactivity, and impulsivity scores was 48.6%, 45.9%, and 45.9%, respectively. Moreover, Fujioka et al [42] reported a significant improvement in ADHD scores during the follow-up period with methylphenidate or Atomoxetine medication for inattentive symptom score, hyperactivity/impulsivity symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Among different versions of this test, we used the Advanced Test of Attention (ATA) that integrates both visual and auditory sensorial modalities, measuring attention, and response inhibition in Korean children older than 5 years (51). The target rate of stimulus presentation is 22% for the first section, 50% for the middle section, and 78% for the last section, with the stimulus presentation time of 0.1 s and an interval of 2 s between the presentations (39,52). This test includes both auditory and visual scores of omission errors (i.e., missed targets), commission errors (i.e., incorrect responses to non-targets), the mean of response time (i.e., response speed), response time variability, response criterion, and detectability (i.e., ability to distinguish targets from non-targets) (39).…”
Section: Advanced Test Of Attentionmentioning
confidence: 99%
“…ATA [34] is widely used in Korea for the diagnosis of ADHD [35]; its usefulness has been verified in Japan [36]. ATA measures visual and auditory attention using a computer and can be executed by children and adolescents aged 5 to 15 years.…”
Section: Advanced Test Of Attention (Ata) and Interactive Metronome (Im)mentioning
confidence: 99%